The Architecture of Cooperation Among Non-kin: Coalitions to Move Up in Nature’s Housing Market - Laidre, Mark E. (Frontiers in Ecology and Evolution, 2021)
The evolution of cooperation among non-kin poses a major theoretical puzzle: why should natural selection favor individuals who help unrelated conspecifics at a cost to themselves? The relevance of architecture to this question has rarely been considered. Here I report cooperation among non-kin in social hermit crabs (Coenobita compressus), where unrelated conspecifics work together to evict larger individuals from a housing market of architecturally remodeled shells. I present (1) the first detailed description of natural coalitions in the wild and (2) a theoretical framework, which examines the evolutionary benefits to each coalition member and predicts when forming a coalition will be successful. In the wild, important ecological and social constraints exist, which are built into the model. Based on these constraints, I show that coalitions can be a successful strategy if several key criteria hold: the coalition is necessary, effective, stable dyadically, and stable polyadically. Notably, the ‘splitting the spoils’ problem—which often undermines non-kin cooperation—is eliminated via architecture: a small individual (C) who helps a medium individual (B) to evict a large individual (A) will ultimately benefit, since C will get B’s left behind shell after B moves into A’s shell. Coalitions, however, can break down due to added layers of social complexity involving third-party ‘free riders’ and ‘cheaters’, which strategically butt in the architectural queue and thereby steal incentives from the smaller coalition member. Overall, therefore, substantial scope exists for both cooperation and conflict within nature’s housing market of architecture. Experiments are now needed to directly test architecture’s impact on coalitions.